2021
DOI: 10.3390/biology10060544
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Mechanisms of Plant Enrichment and Detoxification of Cadmium

Abstract: The heavy metal cadmium (Cd), as one of the major environmentally toxic pollutants, has serious impacts on the growth, development, and physiological functions of plants and animals, leading to deterioration of environmental quality and threats to human health. Research on how plants absorb and transport Cd, as well as its enrichment and detoxification mechanisms, is of great significance to the development of phytoremediation technologies for ecological and environmental management. This article summarises th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 167 publications
(206 reference statements)
0
16
0
Order By: Relevance
“…The results showed that some significant differences exist between the various herbs in HM concentration, depending on whether the plant is annual, or perennial (all selected medicinal herbs investigated in our paper are perennial), the used part, and plant families. The perennial herbs, such as thyme, blueberry, dog rose, or winter savory, which accumulate HMs predominantly in roots, and subsequently transfer some portions to other parts of the plant [ 33 , 34 ], can be expected to have higher concentrations of HMs. However, according to our analysis, the HM concentrations in these herbs highly depend on the location and the type of HM.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that some significant differences exist between the various herbs in HM concentration, depending on whether the plant is annual, or perennial (all selected medicinal herbs investigated in our paper are perennial), the used part, and plant families. The perennial herbs, such as thyme, blueberry, dog rose, or winter savory, which accumulate HMs predominantly in roots, and subsequently transfer some portions to other parts of the plant [ 33 , 34 ], can be expected to have higher concentrations of HMs. However, according to our analysis, the HM concentrations in these herbs highly depend on the location and the type of HM.…”
Section: Resultsmentioning
confidence: 99%
“…Cd stress leads to the excessive accumulation of ROS in plants, which damage lipids and protein nucleic acids and influence the growth and development of plants, while miRNAs play a key role as post-transcriptional regulators of genes involved in antioxidant response pathways [ 97 ]. miRNA eliminates ROS by targeting and regulating the expression of related genes, such as superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), non-enzymatic components, ascorbic acid (AsA) and GSH [ 34 , 52 ].…”
Section: Role Of Mirnas In Response To CD Toxicitymentioning
confidence: 99%
“…When there is a high accumulation of cadmium in the cell wall, cadmium is transported to the vacuole. Cadmium combines with proteins, organic acids, sugars and other organic substances in the vacuole to form macromolecular compounds through chelation, thereby reducing cadmium toxicity (Riyazuddin et al, 2021;Yang et al, 2021).…”
Section: Chelationmentioning
confidence: 99%